PSYCHOLOGICAL WELL BEING PADA IBU YANG MEMILIKI REMAJA ATTENTION DEFICIT HYPERACTIVITY DISORDER ADHD - Dianita Alvina Zahra; Niken Widi Astuti (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
Background: This research is based on the fact that many parents often feel worried about their child's condition when accompanying the online learning process of children with ADHD. Emotional shocks are also often experienced by parents of ADHD children, such as feelings of resentment, stress, embarrassment, and anger. ADHD. Objective: This study aims to provide an overview of the psychological well-being of mothers with adolescents diagnosed with ADHD. Method: The research employed a descriptive qualitative method using purposive sampling, involving three mothers who met the study criteria. Data were collected through semi-structured interviews, observations, and documentation. Result: The findings indicate that the psychological well-being of these mothers varies. Most participants demonstrated strong personal growth, as they perceived challenges as opportunities for development. However, their sense of purpose in life tended to be low, primarily due to the difficulties their adolescents faced in managing daily activities, slow progress, and lack of motivation. Factors such as social support, family conditions, and socioeconomic status also played significant roles in determining the mothers' psychological well-being. Conclusion: In conclusion, the psychological well-being of mothers is influenced by their ability to adapt to the challenges of raising adolescents with ADHD, as well as the support and socioeconomic status they have. Adequate social support can enhance their psychological well-being and facilitate the caregiving process for their adolescents with ADHD.